Diagnostic Laboratory Testing and Clinical Preparedness for Dengue Outbreaks during the COVID-19 Pandemic - Waterman, Stephen H.; Paz-Bailey, Gabriela; San Martin, Jose L.; Gutierrez, Gamaliel; Castellanos, Luis G.; Mendez-Rico, Jairo A. (The American journal of tropical medicine and hygiene, 2020)
Wilder-Smith et al made key observations regarding the importance of maintaining mosquito control and clinical preparedness for dengue during the COVID-19 pandemic crisis, especially given the resurgence of dengue in Latin America in 2019 and 2020. Clearly, simultaneous outbreaks of COVID-19 and dengue pose high potential for overwhelming healthcare systems; and because the two diseases can have similar nonspecific clinical presentation in early stages, alerting clinicians and putting in place carefully drawn clinical algorithms for triage are critical to reducing mortality. Here, Waterman et al qualify and elaborate on Wilder-Smith et al's comment regarding virologic and diagnostic testing in this context. Given limitations in diagnostic testing for both dengue and COVID-19, suspect febrile illnesses in dengue-endemic areas require patient/family guidance to monitor warning signs of severe illness and to seek evaluation and care if signs of symptoms of either disease occur.